RESEARCH-BASED CO-CURRICULAR MANAGEMENT: A CONCEPTUAL FRAMEWORK FOR IMPROVING STUDENTS' ACADEMIC ACHIEVEMENT - Amirul Akbar; Sukarman Sukarman; Muhammad Khoiruddin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This study examines the implementation of research-based co-curricular management in enhancing students’ academic achievement from an educational management perspective. A qualitative library research approach was employed by analyzing books, scientific journals, policy documents, and previous studies relevant to research-based co-curricular activities and student achievement. Data were analyzed using qualitative content analysis. The findings indicate that effective implementation is achieved through four core management functions: planning, organizing, implementation, and evaluation. These processes enable educational institutions to establish structured research programs that promote students’ critical thinking, analytical skills, creativity, collaboration, and problem-solving abilities. The study also identifies key supporting factors, including competent teachers, adequate facilities, institutional commitment, a supportive academic culture, and collaboration among schools, families, and communities. Overall, well-managed research-based co-curricular activities contribute significantly to improving students’ academic achievement while fostering scientific culture and strengthening twenty-first-century competencies. Therefore, research-based co-curricular management can serve as an effective strategy for sustainable educational quality improvement.